Tantangan Jurnalis Muslim di Era Revolusi Industri 4.0 - Febriany (LPPM IAINU Kebumen, 2019)
The era of the Industrial Revolution 4.0 was felt in various parts of the world, various aspects of the economy, politics, culture and journalism, of course. It also turns out to be a challenge for the media industry. One of them is printing competent and professional journalists. Muslim journalists have their own challenges in this new era. Currently, various kinds of human needs, including information, have implemented the support of the internet and the digital world as a vehicle for interaction and transactions. The challenges faced by Muslim journalists are how to improve quality, actuality, avoid hoaxes, enforce the code of ethics of Muslim journalists and how to package Islamic news to attract audiences. to read it.